Hungarian borderlands : from the Habsburg Empire to the Axis Alliance, the Warsaw Pact, and the European Union /: from the Habsburg Empire to the Axis Alliance, the Warsaw Pact, and the European Union. (2011) - Schubert, Frank N
No abstract available